Pengaruh Promosi terhadap Peningkatan Hasil Penjualan Produk Jasa Perbankan pada Pt. Bank Muamalat Indonesia Tbk - Arsenius Arsenius; Dety Mulyanti (Syntax Idea)
The Bontolempangan community, Buki District, Selayar Islands Regency is a traditional village that still maintains the traditional culture of their ancestors. The marriage system that still exists in the era of globalization is adat attaralu. The purpose of this study is to determine the symbolic meanings contained in the Attaralu custom carried out in Bontolempangan Village, Buki District, Selayar Islands Regency. This research uses qualitative methods through a case study approach with descriptive analysis including collecting data, presenting, displaying data, and drawing conclusions. Data collection was carried out using observation, interview, and documentation techniques. The results of this study show that there are three main processes in the implementation of attaralu customs, namely a'pissalingi, ambaung patingroang, and attaralu, of these three processes have a deep philosophical meaning for the people of Bontolemapangan Village, Buki District, Selayar Islands Regency.